Replication Data for "Designing Better Input Support Programs: Lessons From Zinc Subsidies in Andhra Pradesh, India" - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset includes data and do-files for reproducing results presented in the article "Designing better Input Support Programs: Lessons from Zinc Subsidies in Andhra Pradesh, India." The data used in the analysis of this paper were generated from a survey of 1621 farming households, 78 agricultural input dealers, and 61 government extension workers in six districts—Chittoor, East Godavari, West Godavari, Krishna, Nellore, and Srikakulam—of Andhra Pradesh. The surveys were conducted in Rabi season, 2018-19, and collected data on cultivation practices, the use of chemical inputs including micronutrients over Kharif 2018 and Rabi 2018-19, and awareness about micronutrient benefits from farmers. The surveys of extension workers and fertilizer dealers included questions on the main roles and responsibilities and issues faced in the implementation of the micronutrient subsidy scheme. The data files included are raw data generated from the survey. The "Analysis" do-file will generate constructed variables from the raw data which are described in the S1 Table of the paper. The remaining results, figures (Fig 1-6), and tables (Table 2, Table 3, Table 4, S2 Table) used in the paper can also be reproduced running this do file.